Prediksi Potensi Daya Listrik PLTGL-OWC di Selat Makassar Menggunakan Metode Gradient Boosted Tree-Regression (GBT) - Adellia Juni Astine; Dian Candra Rini Novitasari; Ratna Cintya Dewi (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The increasing demand for electricity continuously emphasizes the importance of developing renewable energy sources. Indonesia, as a country consisting of many islands, has significant potential to utilize energy from ocean waves, one of which is by using Oscillating Water Column (OWC) technology that can convert wave energy into electrical energy. The purpose of this study is to estimate the electrical energy generated by the OWC type Ocean Wave Power Plant (PLTGL) in the Makassar Strait using the Gradient Boosted Tree Regression (GBT) method. Two approach schemes are used in this study, but the focus of the discussion is on the first scheme, namely the indirect approach. In this approach, predictions are first made on four main variables, namely significant wave variables (Hsig), maximum wave height (Hmax), wave period (wave period), and wind speed (wind speed). The results of the main variable predictions are then used to calculate the electrical power generated by the PLTGL-OWC. The maximum power is estimated to be 23,926 Watts on January 3, 2025 at 12:00, and the minimum power is 3,256 Watts on January 7, 2025 at 19:00. This approach is effective for predicting the power output of ocean wave generators in the Makassar Strait.